Pendidikan Holistik: Menggabungkan Literasi Qur’an, Tradisi Keagamaan dan Pemberdayaan Alam di Pondok Pesantren Sadana Padarincang - Ahmad Rifa Ein; Siti Pakitoh; Mus’idul Millah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study explores the shift from traditional to modernist educational paradigms in Islamic boarding schools (pesantren), which have been in existence since before Indonesia’s independence. The shift involves adapting learning methods while retaining traditionalist approaches, ensuring that they meet modern needs without eliminating their core values. The study uses a qualitative-phenomenological approach to examine three main areas: (1) the strategy of educational values and spiritual practices employed by pesantren leaders, with an emphasis on the TAQWA method, which aims to improve student understanding quickly; (2) the integration of Qur'an literacy, religious traditions, and environmental empowerment in the educational process; and (3) the impact of this model on student character development. Qur'an literacy in this context extends beyond reading and memorizing verses, focusing on understanding and actualizing its values in daily life. Religious practices such as book study, worship routines, and etiquette coaching promote moral development. Environmental activities, such as agriculture and natural resource management, encourage independence and ecological awareness. This holistic approach can serve as a model for character education, blending spiritual, social, and environmental aspects, while strengthening pesantren's role in fostering moral and ecological awareness.